PENGEMBANGAN BUKU AJAR SOSIOLOGI BERBASIS KEARIFAN LOKAL SEBAGAI UPAYA PENGUATAN KARAKTER SISWA SMA/MA DI LOMBOK UTARA - Masyhuri Masyhuri; Suud Suud; Muhammad Ilyas (Jurusan P. IPS, FKIP, Universitas Mataram, 2022)
Basic Competencies of Sociology subjects in SMA/MA show the potential for developing local wisdom-based learning as an effort to strengthen students' character. For this reason, it is necessary to prepare learning tools, in the form of textbooks which should also be in accordance with the needs for achieving the intended KD. The textbooks referred to in fact have not been developed by Sociology teachers at SMA/MA in North Lombok. Therefore, a research was conducted with the aim of producing a local wisdom-based sociology textbook that could be implemented as an effort to strengthen the character of SMA/MA students in North Lombok. For this reason, development research was carried out with activity stages, namely needs analysis, drafting of textbooks, validation tests by a team of experts, and revisions. The results of the study show that textbooks based on local wisdom are needed because they are a necessity to help students achieve the predetermined KD. Textbooks based on local wisdom of the people of North Lombok are also not yet available. This makes Sociology learning in SMA/MA in North Lombok not contextual, and does not contribute to strengthening students' character. Based on the needs analysis, a draft textbook for class XII semester II which consists of two chapters is drawn up according to the number of KD knowledge that is targeted to be achieved in that semester. The innovation in the textbook is to integrate the local wisdom of the people of North Lombok to illustrate the various existing materials, so that the material in the textbook is interesting, easy to understand and meaningful, which is not only building knowledge but also as an effort to strengthen character. The results of expert assessments of textbooks are very good and are ready to be tested for their effectiveness, which is planned for the next stage of research.